DNA display of glycoconjugates to emulate oligomeric interactions of glycans - Novoa, Alexandre; Winssinger, Nicolas (Beilstein Journal of Organic Chemistry, 2015)
Glycans (carbohydrate portion of glycoproteins and glycolipids) frequently exert their function through oligomeric interactions involving multiple carbohydrate units. In efforts to recapitulate the diverse spatial arrangements of the carbohydrate units, assemblies based on hybridization of nucleic acid conjugates have been used to display simplified ligands with tailored interligand distances and valences. The programmability of the assemblies lends itself to a combinatorial display of multiple ligands. Recent efforts in the synthesis and applications of such conjugates are discussed.
Keywords: glycan; glycoconjugate; DNA display; multivalency; nucleic acid conjugates; oligomeric interaction